A patient‐centred approach to biological treatment decision making for psoriasis: an expert consensus. (14th September 2015) - Strohal, R.; Prinz, J. C.; Girolomoni, G.; Nast, A.
Abstract: Background: Each individual psoriasis patient has different expectations and goals for biological treatment, which may differ from those of the clinician. As such, a patient‐centred approach to treatment goals remains an unmet need in psoriasis. Objective: The aim of this study was to review available data on patients' and physicians' decision criteria and expectations of biological treatment for moderate‐to‐severe psoriasis with the aim of developing a core set of questions for clinicians to ask patients routinely to understand what is important to them and thus better align physicians' and patients' expectations of treatment with biologics and its outcomes. Methods: A literature search was conducted to identify key themes and data gaps. Aspects of treatment relevant when choosing a biological agent for an individual patient were identified and compared to an existing validated instrument. A series of questions aimed at helping the physician to identify the particular aspects of treatment that are recognised as important to individual psoriasis patients was developed. Results: Key findings of the literature search were grouped under themes of adherence, decision‐making, quality of life, patient/physician goals, communication, patient‐reported outcomes, satisfaction and patient benefit index. Several aspects of treatment were identified as being relevant when choosing a biological agent for an individual patient. The questionnaire is devised in two parts. The first part asks questions about patients' experience of psoriasis and satisfaction with previous treatments. The second part aims to identify the treatment attributes patients consider to be important and may as such affect their preference for a particular biological treatment. The questionnaire results will allow the physician to understand the key factors that can be influenced by biological drug choice that are of importance to the patient. This information can be used be the physician in clinical decision making. Conclusion: The questionnaire has been developed to provide a new tool to better understand and align patients' and physicians' preferences and goals for biological treatment of psoriasis.